2012
DOI: 10.1038/bjc.2011.580
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of population-based screening for colorectal cancer: a comparison of guaiac-based faecal occult blood testing, faecal immunochemical testing and flexible sigmoidoscopy

Abstract: Background:Several colorectal cancer-screening tests are available, but it is uncertain which provides the best balance of risks and benefits within a screening programme. We evaluated cost-effectiveness of a population-based screening programme in Ireland based on (i) biennial guaiac-based faecal occult blood testing (gFOBT) at ages 55–74, with reflex faecal immunochemical testing (FIT); (ii) biennial FIT at ages 55–74; and (iii) once-only flexible sigmoidoscopy (FSIG) at age 60.Methods:A state-transition mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 71 publications
(104 reference statements)
1
88
0
Order By: Relevance
“…This is especially true since inherited CRC has an accelerated adenoma-carcinoma sequence compared to the slower oncogenesis in sporadic CRC [27]. Sigmoidoscopy can detect premalignant adenomas and a single examination at age 60 is very cost-effective way to screen for CRC in the general population [28]. However, since most hereditary CRC cases are found proximal of the splenic flexure, sigmoidoscopy is not an option in surveillance for HCRC or FCRC.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true since inherited CRC has an accelerated adenoma-carcinoma sequence compared to the slower oncogenesis in sporadic CRC [27]. Sigmoidoscopy can detect premalignant adenomas and a single examination at age 60 is very cost-effective way to screen for CRC in the general population [28]. However, since most hereditary CRC cases are found proximal of the splenic flexure, sigmoidoscopy is not an option in surveillance for HCRC or FCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Even though several tests for CRC screening exist, their participation rates remain suboptimal [5,6] . Population screening programs include endoscopic procedures (i.e., colonoscopy, flexible sigmoidoscopy or colon video capsule endoscopy), radiologic tests, including barium enema and computed tomography-colonography and fecal tests, such as the fecal occult blood test (FOBT) and FIT.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on the cost-effectiveness of the various CRC screening modalities yielded mixed results. 26,[37][38][39][40][41][42][43] Some reported that screening based on FS was the most cost-effective, [37][38][39] whilst other studies found that colonoscopy screening had greater cost-effectiveness. 26,40,41 Yet one study reported that a hybrid method using yearly rehydrated faecal occult blood tests coupled with FS was amongst the most cost-effective.…”
Section: Discussionmentioning
confidence: 99%